Моделирование электротоковых микрореле - Mukhurov, N. I.; Yefremov, G. I.; Zhvavyi, S. P. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The design and method of electrocurrent microrelay theoretical modelling is offered. It is established, that base function in the normalized kind graphically represents a symmetric parabola. Microrelay capability evaluation have been carried out for different current flow directions through the meander-line system of planar structure.